(untitled) (Nordic Journal of African Studies, 2011)
Somali migrants do not always succeed in meeting the high expectations of their families and communities. This article focuses on this “failed diaspora”, i.e. the experiences of those Somali migrants who have been deported or returned to Somaliland, either by authorities or their families, because of criminal behaviour, mental illness, drug abuse or life styles that Somali parents cannot accept. It is hoped that they will recover in Somaliland by being “returned to culture” or by receiving religious and traditional treatments. In the diaspora a Somali migrant continues to belong to an extended Somali family, its values and networks, and the family may make strategic decisions on behalf of an individual. Ultimately, the success of a transnational Somali family is dependent on the behaviour, achievements and resources of its individual members. This article is based on a total of 6 months ethnographic fieldwork that was carried out in Somaliland in 2005–2011.